Determination of fuel consumption of an ice with electromechanical injectors and a deadlock type ramp on transients - Savenkov N.V.; Zolotarev O.O. (Naučno-Tehničeskij Vestnik Brânskogo Gosudarstvennogo Universiteta)
The internal combustion engine operates in unsteady modes for a significant part of the time when the vehicles is moving. This is unavoidable for vehicles with traditional power plants for the following reasons: 1) the need to regulate the power on the driving wheels, 2) the effective performance and environmental qualities of the engine in unsteady modes are often worse in relation to those in steady-state modes of operation; this is due to the influence of many factors and has been studied in many well-known scientific papers. Experimental studies of current fuel consumption, effective torque and environmental qualities of the engine at unsteady speeds are relevant. This is due to the complexity of the processes that take place in the units. Their main goal of these studies is to ensure greater adaptability of the internal combustion engine and power plant to work in unsteady modes. The methodology for determining the current fuel consumption when operating in an unsteady mode of an automobile internal combustion engine with external mixing and a dead-end fuel ramp with distributed gasoline injection through electromechanical injectors is improved in this article. An experimental study was carried out in the work. The injectors of the Denso 23209-39295 model of the 2ZR-FXE engine of the Toy-ota Prius PHV 4th generation vehicles is selected as an example. The fuel pressure drop, the duration of the electric control pulse and the magnitude of the electric voltage are considered as parameters that affect the volumetric performance of the injectors. The Autool ST160 stand and additional electronic equipment devel-oped by the authors were used in the study. The result of the study is an analytical device for more accurate determination of the current fuel consumption in unsteady engine operating modes. The improved technique does not require the installation of additional sensors and equipment on the vehicles.